Kepuasan Mahasiswa Sebagai Intervening Antara Kualitas Layanan Dan Citra Institusi Dengan Retensi - Audina, Susmita; Jariah, Ainun (Jurnal Ilmu Manajemen Advantage, 2017)
Abstract: This research has a result multiple regression model is y = (0,079X1 + (-0,064)X2 + 0,279Y1 + 0,833. The result of this research showed that on the partial only quality service can be influence to student satisfaction. Institutions image can be influence to student satisfaction. But, event simultaneously service quality and image institution has a significant to student satisfaction. The quality service and image institution with partialand simultaneously did not influence to retentiton. Ovel all the quality service and image institution using student satisfaction did not influence significant to retention.